2015
DOI: 10.1007/s10597-015-9842-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Psychosis: Prevalence and Associated Factors in a Nigerian Clinical Population

Abstract: Aim of the study was to assess sociodemographic and clinical determinants of quality of life in psychotic patients in a general hospital population in Nigeria. Information was obtained on demography, duration of untreated illness (DUI) and functioning among Schizophrenia (368), schizoaffective disorder (70), and 214 patients with affective psychosis. Functioning was assessed using GAF, severity of psychopathology with PANSS and quality of life using WHOQoL-BREF. In general, the differences in the QoL across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…). Similarly, in Nigeria, a large proportion of people with schizophrenia had not received treatment (Lasebikan & Owoaje ; Onofa et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…). Similarly, in Nigeria, a large proportion of people with schizophrenia had not received treatment (Lasebikan & Owoaje ; Onofa et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Global functioning predicted QoL overall in most analyses (Alessandrini et al, 2016, Kusel et al, 2007, Lasebikan & Owoaje, 2015, Meijer et al, 2009, Norman et al, 2000, Rocca et al, 2016, Roe et al, 2011, Woon et al, 2010. Exceptions were Stubbs et al (2015) andPrince (2007).…”
Section: Functioning As Predictor Of Qolmentioning
confidence: 96%
“…Schizophrenia was the single diagnosis in 26 articles (62%), only four articles (Greenley et al, 1997, Holloway & Carson, 1999, Lasebikan & Owoaje, 2015, Stubbs et al, 2015 10%included participants with bipolar disorder or depressive disorder with psychotic symptoms.…”
Section: Data Extracted Overviewmentioning
confidence: 99%
“…10 Some studies have found that medication side effects are one factor which could influence the quality of life for people with schizophrenia. 5,11,12 In addition, previous studies suggest that nonad-herence to antipsychotic medications may result in poor quality of life in patients with schizophrenia (Lasebikan & Owoaje, 2015). 13 Nonadherence to antipsychotic medications is a major factor that contributes to relapse and readmission.…”
Section: Introductionmentioning
confidence: 99%
“…5,11,12 In addition, previous studies suggest that nonad-herence to antipsychotic medications may result in poor quality of life in patients with schizophrenia (Lasebikan & Owoaje, 2015). 13 Nonadherence to antipsychotic medications is a major factor that contributes to relapse and readmission. 14,15 However, previous study suggests that many patients with schizophrenia are reported to experience dissatisfaction with mental health care providers and that a lack of access significantly predicted medication omission.…”
Section: Introductionmentioning
confidence: 99%